A hybrid-membrane migration method to isolate high-purity adipose-derived stem cells from fat tissues - Higuchi, Akon; Wang, Ching Tang; Ling, Qing Dong; Lee, Henry Hsin Chung; Kumar, S. Suresh; Yung, Chang; Alarfaj, Abdullah A.; Munusamy, Murugan A.; Hsu, Shih Tien; Wu, Gwo Jang; Umezawa, Akihiko (Nature Publishing Group, 2015)
Human adipose-derived stem cells (hADSCs) exhibit heterogeneous characteristics, indicating various genotypes and differentiation abilities. The isolated hADSCs can possess different purity levels and divergent properties depending on the purification methods used. We developed a hybrid-membrane migration method that purifies hADSCs from a fat tissue solution with extremely high purity and pluripotency. A primary fat-tissue solution was permeated through the porous membranes with a pore size from 8 to 25 μm, and the membranes were incubated in cell culture medium for 15-18 days. The hADSCs that migrated from the membranes contained an extremely high percentage (e.g., >98%) of cells positive for mesenchymal stem cell markers and showed almost one order of magnitude higher expression of some pluripotency genes (Oct4, Sox2, Klf4 and Nanog) compared with cells isolated using the conventional culture method.